Preparation and characterisation of WC-10Co powders obtained by aqueous milling. Issue 18 (15th December 2018) - Chicinaş, H.F.; Marinca, T.F.; Mesaroş, A.; Götze, P.; Eckert, A.; Stoian, G.; Leoştean, C.; Pană, O.; Lupu, N.; Popa, C.O.
Abstract: This paper presents a new approach on the wet attrition of some composite WC-10Co powders by using an aqueous medium instead of the classical organic solvent based processing method. The hard metal powders have been characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM), laser particle size analysis (PSA), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis coupled with mass spectrometry (TG-MS). The XRD investigation revealed that no significant changes in the structure of the material occur during milling, while the SEM and PSA analysis highlighted the presence of agglomerates that are formed during the drying of the aqueously processed powders. The observed composite flakes are formed by the sequential cold-welding and fracturing process of the particles. The elemental powders were blended and milled together in an aqueous media (distilled water + corrosion inhibitor) in order to achieve a homogeneous dispersion of the constituents. Prolonged milled durations are resulting in an incremental oxidation process, leading to the formation of CoO(OH). XPS analyses revealed that Co oxidises in depth, as opposed to the sample obtained by classical route, which reveals only superficial oxide. The residual moisture evidenced by TG-MS could also favour the formation of agglomeration and oxide in the powder.